SIKAP MASYARAKAT DAN KONSERVASI: SUATU ANALISIS KEDAWUNG (Parkia timoriana (DC) Merr.) SEBAGAI STIMULUS TUMBUHAN OBAT BAGI MASYARAKAT, KASUS DI TAMAN NASIONAL MERU BETIRI - Ervizal Amzu; Kurnia Sofyan; Lilik Budi Prasetyo; Hariadi Kartodihardjo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2007)
Ten years of direct experience in Meru Betiri National Park has shown that conservation and community’s attitude was closely related formed one action unit. This research tested whether pendarungs6) and managers understood the signals released by kedawung in its habitat and used those signals as stimulus for their attitudes and actions to conserve kedawung. In fact the conservation of kedawung had not happened yet. The maintained and sustainable use of the kedawung was reflection of the community’s attitudes that the crystallization stimulus with attitude components, as cognition, affection and overt action (tend to act). The strong stimulus of kedawung for its conservation attitudes are (1) natural stimulus, (2) useful stimulus and (3) religious stimulus. There were biases the experiences and knowledge of the pendarungs and the managers, which originated in the biases of kedawung’s stimulus comprehension. Manager of the national park has not much delved the experience of the old generation of the local community. This had caused lack of feedback to the community and the current conservation action did not comply with the stimulus happening in the national park. The strong stimulus has weakened in the pendarung, except the stimulus related to economical values. These problems happened have been caused by the discontinuity of the local knowledge, changing generations and lack of community’s acces to biodiversity resources of the national park. The implication of these results should be (1) to improve of the community’s cognition through the development and continuity of the local knowledge to the modern knowledge based on characteristics of the local’s resources, (2) to improve the policy for the national park management.Keywords: Stimulus, attitude, community, pendarung, kedawung and conservation.